2003
DOI: 10.1063/1.1611276
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh magnetic field sensitivity in laminates of TERFENOL-D and Pb(Mg1/3Nb2/3)O3–PbTiO3 crystals

Abstract: It has been found that laminate composites of longitudinally magnetized magnetostrictive TERFENOL-D and a transversely poled piezoelectric Pb(Mg1/3Nb2/3)O3–PbTiO3 crystal have extremely high magnetic field sensitivity. At room temperature, an output voltage with an exceptionally good linear response to an ac magnetic field Hac was found over the range of 10−11<Hac<10−3 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
168
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 286 publications
(171 citation statements)
references
References 19 publications
2
168
1
Order By: Relevance
“…These values of ME voltage coefficients achieved from Fe-Ga/PZT laminates are comparable to, or slightly higher than, previous reports for Terfenol-D/PZT and CFO-NFO/PZT laminates. [17][18][19][20][21][22][23][24][25][26][27][28][29] …”
Section: E Frequency Dependence Of Me Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These values of ME voltage coefficients achieved from Fe-Ga/PZT laminates are comparable to, or slightly higher than, previous reports for Terfenol-D/PZT and CFO-NFO/PZT laminates. [17][18][19][20][21][22][23][24][25][26][27][28][29] …”
Section: E Frequency Dependence Of Me Responsementioning
confidence: 99%
“…Lett., [12][13][14][15][16] and other high-impact journals. The magnetoelectric ͑ME͒ effect is a polarization P response to an applied magnetic field H, or conversely a magnetization M response to an applied electric field E. Previously, ME effects have been reported in composites of piezoelectric Pb͑Zr, Ti͒O 3 [17][18][19][20][21][22][23][24][25][26][27][28][29] In this article, we will show that laminate composites of magnetostrictive Fe-20 at. % Ga crystals and piezoelectric PZT ceramics also have a large ME coupling.…”
Section: Introductionmentioning
confidence: 99%
“…7 Different combinations of relative directions of the magnetization and polarization of various piezoelectric ͓for example, Pb͑Zr, Ti͒O 3 ͑PZT͔͒ and magnetostrictive phases ͑for example, metglas͒ have been attempted so far. [8][9][10] For example, the push-pull mode is a combination that consists of a structure with a longitudinally magnetized magnetic layer and a symmetrically poled piezoelectric layer about its central nodal point in reverse directions along the longitudinal axis. It has been found that three layer metglas-PZT-metglas structures offer the highest ME voltage coefficient and magnetic field sensitivity.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, to date, investigations of ME laminate composites have focused on passive sensors, 6,12,14 rather than high-power device applications. Also, previously, only ME materials with low coupling have been found.…”
mentioning
confidence: 99%